Impact of the coffee berry borer on the volatile and semi-volatile compounds; qualitative profile of Coffea arabica berries - Claudia Patricia Ruiz-Diaz; José C. Verle Rodrigues; Erick Miro-Rivera; Liz M. Diaz-Vazquez (Food Chemistry Advances, 2023)
One of the main attributes that highlight the final quality of a gourmet cup of coffee is its aroma. Aromas vary according to a variety of plant and environmental variables, among others. This study aimed to characterize volatile and semivolatile compounds according to the Coffee arabica ''Limani'' berries ripening stages (healthy and brocaded). The study used different extraction methodologies to capture the broad spectrum of volatile, semivolatile organic compounds in coffee berries and berry borer (CBB). The methodologies used in the study included: enfleurage, headspace SPME (solid-phase microextraction), absorbent trap, and direct immersion SPME. Our study generated a Profile for coffee berries and CBB w with 228 compounds. Esters, cyclic, and benzyl compounds represent 65.6% of the total. The first three types of compounds that most attract our sense of smell constitute 40.5% of the compounds found; 1.3% aldehydes, 2.6% alcohols, and 36.6% benzyl. Overripe berries have high volatile emissions and show a composition dominated mainly by esters followed by alcohols, ketones, and aldehydes. The lowest-level compounds were monoterpenes. The number of compounds found in CBB varied according to sex. In summary, the CBB damage harms coffee berries' quality and aroma. The complete profile compounds generated will help better understand insect-plant relationships and potentially develop effective bait traps.